Familial Mediterranean fever responds well to infliximab - Ozgocmen, S; Özçakar, L; Ardicoglu, O; Kocakoc, E; Kaya, A; Kiris, A (Springer, 2006)
The most common arthritic involvement in familial Mediterranean fever (FMF) is acute recurrent monoarthritis; however, sometimes spondyloarthropathy-like findings or typical ankylosing spondylitis may also ensue. Reported here is our favorable experience with infliximab in an FMF patient who had been resistant to colchicine and disease-modifying antirheumatic drugs (sulfasalazine and methotrexate) treatments. A 72-week follow-up of the patient yielded complete remission of the febrile abdominal episodes, and spondylitis responded well. The patient's bilateral aseptic necrosis of the femoral head deteriorated and caused hip pain, discomfort, and disability. Overall, we believe that tumor necrosis factor (TNF) alpha has an important role in the disease pathogenesis and also that anti-TNF may represent a promising robust treatment alternative in FMF.
Keywords: aseptic necrosis; familial Mediterranean fever; infliximab; spondylitis